Association of blood pressure in late adolescence with subsequent mortality: cohort study of Swedish male conscripts. (22nd February 2011) - Sundström, Johan; Neovius, Martin; Tynelius, Per; Rasmussen, Finn
Abstract : Objective To investigate the nature and magnitude of relations of systolic and diastolic blood pressures in late adolescence to mortality. Design Nationwide cohort study. Setting General community in Sweden. Participants Swedish men (n=1 207 141) who had military conscription examinations between 1969 and 1995 at a mean age of 18.4 years, followed up for a median of 24 (range 0-37) years. Main outcome measures Total mortality, cardiovascular mortality, and non-cardiovascular mortality. Results During follow-up, 28 934 (2.4%) men died. The relation of systolic blood pressure to total mortality was U shaped, with the lowest risk at a systolic blood pressure of about 130 mm Hg. This pattern was driven by the relation to non-cardiovascular mortality, whereas the relation to cardiovascular mortality was monotonically increasing (higher risk with higher blood pressure). The relation of diastolic blood pressure to mortality risk was monotonically increasing and stronger than that of systolic blood pressure, in terms of both relative risk and population attributable fraction (deaths that could be avoided if blood pressure was in the optimal range). Relations to cardiovascular and non-cardiovascular mortality were similar, with an apparent risk threshold at a diastolic blood pressure of about 90 mm Hg, below which diastolic blood pressure and mortality were unrelated, and above which risk increased steeply with higher diastolic blood pressures. Conclusions In adolescent men, the relation of diastolic blood pressure to mortality was more consistent than that of systolic blood pressure. Considering current efforts for earlier detection and prevention of risk, these observations emphasise the risk associated with high diastolic blood pressure in young adulthood.